Control interno a la gestión de cartera de crédito de clientes de la cooperativa de ahorro y crédito “29 de octubre” Ltda. Del cantón Quevedo año 2023. - Pizco García, Diana Roxana (2025)
Internal control in the management of the credit portfolio is a fundamental pillar for the financial health, operational transparency and sustainable growth of credit unions, in addition to the need for solid and effective strategies that complement a good management of the different processes allows the development of business objectives. The objective of this research is to evaluate the impact of internal control on the management of the credit portfolio of customers of the Savings and Credit Cooperative "29 de Octuber" Ltda. of the canton of Quevedo during the year 2023. To this end, a methodology with a qualitative approach of a descriptive nature was adopted, where interviews and COSO I questionnaires were used, applied to the representatives of the credit area of the institution. As a result, it is evident that there is good internal control, but there is a need to combat external factors and internal risks to improve the perception of customers, which is the axis of the cooperative, where the management carried out in the department is benefited by using mechanisms that improve procedures and business growth. As a conclusion, it was evident that the established procedures are adequate, but the risks caused by direct factors that significantly affect must be mitigated, such as a constant problem such as insecurity and the uncertainty of the country's financial risks. In the current business context, an adequate and systematic control of all its operations is carried out, efficiently fulfilling its activities in the credit department in an organized and efficient manner.